Role of Osteopontin and CA125 for early detection of Ovarian Tumor - dubey, Ruchira; tripathi, Sandeep; BJ, Sushma; jha, Om Prakash; agarwal, Rajni (Journal of Neonatal Surgery, 2025)
Introduction: There is a significant rate of morbidity and mortality linked to ovarian cancer. This is because there are no reliable screening techniques and the symptoms are vague. Although it has its own limitations, carbohydrate antigen-125 (CA125) is being employed as a tumor biomarker for the detection of ovarian cancer. Therefore, more tumor indicators are required for ovarian cancer detection. AIM: The study's goal was to evaluate the role of plasma osteopontin (OPN) and CA125 in subjects with ovarian cancer and compare its efficacy with CA125. Methods and Materials: This is a prospective, cross-sectional assessment of a diagnostic test. Suspected instances were women whose adnexal masses were found by radiological or clinical testing. As controls, women who had other gynecological issues were included. All enrolled subjects had their OPN and CA125 levels tested. Results: Among 70 women enrolled, 16 were ovarian cancer, 19 had benign ovarian masses, and 35 were controls. Median plasma CA125 levels were higher in subjects with ovarian cancer (480±418.48). Median plasma OPN levels were higher in subjects with ovarian cancer (4809.84 ±5273.33). The sensitivity and specificity of OPN were 94.30 % and 97.10%, and CA125 77.10% & 85.70 % respectively, with AUC 0.927 (0.846–1.00) and 0.858 (0.769-0.946). Conclusion: OPN levels were higher in ovarian cancer than in the benign ovarian mass and had better specificity than CA125. OPN can better differentiate between benign and malignant ovarian mass as compared to CA125.